Morphological variability of the 11th generation strain of nile tilapia, (Oreochromis niloticus) and traditional genetically improved farmed tilapia (Journal of the Bangladesh Agricultural University, 2012)
To investigate the morphological variations 12 morphometric and 11meristic characters were studied for 100 individuals of the same age of traditional strain GIFT (5th generation) and recently developed 11th generation strain    (GIFU) of Nile tilapia, Oreochromis niloticus. No significant difference was found between total length and other body measurements at 5% level. However, GIFU showed faster linear growth on body depth, maximum body circumference and minimum body circumference where GIFT showed faster linear growth on standard length and head length. On meristic characters, notable variations were observed in case of scale above and below the lateral line, where GIFU individuals showed greater number of scales in both cases. The total length and body weight relationship of both the strains were found to be straight line in logarithmic scales. The mean values of condition factor (K) have been found to be 1.671 for GIFT and 1.711 for GIFU and the mean values of relative condition facto (Kn) were 1.001 and 1.002 for GIFT and GIFU respectively. Findings of the present study suggested the variability of strain GIFU and GIFT in some important parameters.   DOI: http://dx.doi.org/10.3329/jbau.v9i2.11050   J. Bangladesh Agril. Univ. 9(2): 345349, 2011